One-Year Results of the BeweegKuur Lifestyle Intervention Implemented in Dutch Primary Healthcare Settings. (25th August 2015) - Schutte, Bianca A. M.; Haveman-Nies, Annemien; Preller, Liesbeth
Abstract : Background . Lifestyle interventions focusing on healthy diet and physical activity (PA) are effective in reducing health risks in controlled research settings. The aim of this study was to investigate the one-year results of the BeweegKuur lifestyle intervention implemented nationwide in Netherlands for people with a weight-related health risk. Materials and Methods . Data were requested from all 160 locations participating in the BeweegKuur . In a one group pretest/posttest study, one-year changes in health outcome variables and time spent on physical activity were tested with dependent t -tests. Associations between one-year changes in weight and waist circumference and sociodemographic factors and uptake of the program were analysed with ANOVA. Results . Data for 517 participants from 47 locations were available for analysis. One year after the intervention, weight reduced by 2.9 kg (95% CI −3.3;, −2.5), waist circumference by 4.3 cm (−4.9; −3.7), and blood glucose by 0.5 mmol/L (−0.8; −0.3). Physical activity increased significantly. Higher uptake of the program was associated with a larger decrease in waist circumference. Conclusion . The results of the study suggest that lifestyle interventions implemented in real-life primary healthcare settings with tailor-made supervision can contribute meaningfully to primary prevention.